2000
DOI: 10.1037/0022-006x.68.2.241
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of spit tobacco users with transdermal nicotine system and mint snuff.

Abstract: The purpose of this study was to examine the effects of nicotine patch and mint snuff (a nonnicotine product) on craving, withdrawal symptoms, and treatment outcome. This study involved a 2 x 2 factorial design, with Active Nicotine Versus Placebo Patch as one of the factors and Mint Snuff Versus No Mint Snuff as the other factor. Spit tobacco users (N = 402, n = 100-101 in each condition) were randomly assigned to 1 of the 4 treatment conditions for a period of 10 weeks. Treatment outcome was measured up to 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
1
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 25 publications
3
57
1
1
Order By: Relevance
“…Behavioral interventions have reported 12-month quit rates ranging between 10.2% and 34.5% (Severson, 2003). A comparable intervention involving NRT and behavioral therapy reported 37.9% quit rates at 6 months (Howard-Pitney, Killen, & Fortmann, 1999), while another study examining NRT observed 29% abstinence, biochemically verified, 12 months after the intervention's end in individuals using active nicotine patches (Hatsukami et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Behavioral interventions have reported 12-month quit rates ranging between 10.2% and 34.5% (Severson, 2003). A comparable intervention involving NRT and behavioral therapy reported 37.9% quit rates at 6 months (Howard-Pitney, Killen, & Fortmann, 1999), while another study examining NRT observed 29% abstinence, biochemically verified, 12 months after the intervention's end in individuals using active nicotine patches (Hatsukami et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…94,95 Mint and other herbal non-nicotine moist snuff does not enhance treatment outcomes when used with NRT patches, but it does reduce cravings and withdrawal symptoms. 96,97 Consistency is the most important factor. Ask every patient (especially adolescents) on each visit if they use tobacco.…”
Section: Smokeless Tobacco Usersmentioning
confidence: 99%
“…Results from other smokeless tobacco trials have reported the value of NRT in reducing withdrawal symptoms and NRT-related adverse events during quit attempts [13][14][15][16][17][18][19]. Participant satisfaction with English NHS SSS has been reported previously to be high [23,33].…”
Section: What Is Already Knownmentioning
confidence: 92%
“…NRT patch and gum use was observed to reduce withdrawal symptoms both in range and intensity compared to placebo. NRT-related adverse events were reported as minimal, more likely to be heartburn or gastroesophageal reflux if lozenges were used [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%